Active Labor Market Policy in Indonesia: Challenges of the Pre-Employment Card, Wage Subsidy, and Job Loss Insurance Programs (Jurnal Perencanaan Pembangunan: The Indonesian Journal of Development Planning, 2025)
Active Labor Market Policy (ALMP) has become a key instrument in addressing employment challenges in Indonesia, particularly in the aftermath of the COVID-19 pandemic and the enactment of the Omnibus Law on Job Creation in 2020. This study analyzes the implementation, constraints, and impacts of three main ALMP programs—Pre-Employment Card (Kartu Prakerja), Wage Subsidy (BSU), and Job Loss Insurance (JKP)—on worker welfare. Employing a qualitative literature-based approach, data were gathered from academic journals, government reports, and ministerial-level statements. Findings indicate that these programs improved workers' skills and financial stability, though they also faced challenges such as low digital literacy, weak data validity, and suboptimal interagency coordination. The study recommends improved program design, enhanced digital infrastructure, and continuous evaluation to maximize long-term impacts.